PENGARUH PERSEPSI DIRI TERHADAP KEMAMPUAN BERNEGOSIASI DALAM MATAKULIAH SALESMANSHIP PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - MAHARDITA H, ANGGUN (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
For students of marketing and manajemen class, negotiation skill is one of the ability that people must have. Someone who has negotiation skill will be easy to give an argument or convince the others. Many things can affect negotiation skill, one of them is self perception. This research has been done at Universitas Negeri Surabaya. It aims to learn about influence of self perception to negotiating ability of Economic Faculty of Universitas Negeri Surabaya„s students. The research is a quantitative research, which subject are students of marketing and manajemen class at . The determination of the sample using proportional sampling technique, which taken by 155 respondents. It uses questionnaire and documentation to collect data and analize by simple regression Keyword : Self perception, Negotiating ability, Salesmanship.